2010
DOI: 10.1056/nejmsa1004404
|View full text |Cite|
|
Sign up to set email alerts
|

Temporal Trends in Rates of Patient Harm Resulting from Medical Care

Abstract: In a study of 10 North Carolina hospitals, we found that harms remain common, with little evidence of widespread improvement. Further efforts are needed to translate effective safety interventions into routine practice and to monitor health care safety over time. (Funded by the Rx Foundation.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
684
5
21

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,005 publications
(727 citation statements)
references
References 25 publications
17
684
5
21
Order By: Relevance
“…Recent studies suggest that, despite the increased focus on medical errors and investigation, hospitals are not getting safer (Landrigan et al 2010). While we cannot draw a causal connection from our results to this finding, by improving individuals' ability to learn from prior experience, it may be possible to improve future outcomes.…”
Section: Theoretical Contributions and Managerial Implicationsmentioning
confidence: 99%
“…Recent studies suggest that, despite the increased focus on medical errors and investigation, hospitals are not getting safer (Landrigan et al 2010). While we cannot draw a causal connection from our results to this finding, by improving individuals' ability to learn from prior experience, it may be possible to improve future outcomes.…”
Section: Theoretical Contributions and Managerial Implicationsmentioning
confidence: 99%
“…1,2 Consistent decreases in adverse events have not been achieved. 3 In this context, increased attention has been placed on high reliability, a concept that includes achieving consistently high performance levels, 4 not only through reducing failures, but also through improving recognition and action when failures occur. 5 High reliability organizations are characterized by real-time operational awareness, recognition of task complexity, use of near-misses to identify improvement targets, deference to expertise, and resilience among individuals throughout the organization.…”
Section: Introductionmentioning
confidence: 99%
“…It has been defined as Bthe cognitive operations allowing clinicians to observe, collect, and analyze information that ultimately leads to an action.^1 3 However, just as clinical reasoning may be considered broader in scope than decision making, sensemaking may be considered broader than clinical reasoning. Sensemaking encompasses not only understanding individual patients, but also making sense of the competing tasks required by a group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, that did not make the care any better. Two subsequent meticulously performed studies of 2010, albeit with much smaller numbers of patients than in the HMPS, have borne out the estimates in To Err is Human [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, hope and reality collided in two reports, one by HHS and the other from Harvard published in 2010 [7,8]. They showed that the number of deaths associated with adverse events in the decade after To Err is Human was not smaller and may have increased.…”
Section: Introductionmentioning
confidence: 99%